Diametral Tensile and Compressive Strengths of Several Types of Core Materials - Bulem YuÃƒâ€šÃ‚Â¨ zuÃƒâ€šÃ‚Â¨ guÃƒâ€šÃ‚Â¨ lluÃƒâ€šÃ‚Â¨ , DDS, PhD,1 YalcÃƒâ€šÃ‚Â¸ Ãƒâ€žÃ‚Â±n CÃƒâ€šÃ (Journal of Prosthodontics, 2008)
Compressive and diametral tensile strengths (DTSs) of core materials are thought to be important, because cores usually replace a large bulk of tooth structure and should provide sufficient strength to resist intraoral tensile and compressive forces.